Photoluminescence and dielectric properties of (Al/Cu) and (In/Cu) co-doped ZnO sprayed thin films under the oxygen deficiency conditions. (February 2021) - Askri, B.; Riahi, I.; Mimouni, R.; Amlouk, M.
Abstract: This work focuses on the study of the transport of charge carriers in Al (1%)/Cu (1%) and In (1%)/Cu (1%) co-doped ZnO thin films prepared on glass substrates heated at 460 °C using the spray pyrolysis method. Each ratio of doping element is equal to 1% (M/Zn = 1%, M = Al, In, Cu) in the starting solutions. First, SEM and AFM micrographs confirm that the surface samples are rough. Second, the impedance spectroscopy was used to investigate the transport of charge carriers through grains and grain boundaries regions. Indeed, the ε "(T) plots show the appearance of a peak when the temperature increases showing the detrapping phenomenon which may promote the conductive behavior of these co-doped-ZnO thin layers. This behavior was well approved by an increase of the Ac conductivity with temperature for such co-doped films. Finally, PL investigations showed that these doping elements increase the defects density and promote the presence of shallow traps levels close to the conduction band edge which can contribute to the increase of the electrical conductivity. Finally, it is found that indium doping enhances the blue emission intensity by increasing the charge carrier's concentration in oxygen vacancy levels. These oxygen deficiencies have an important effect on the transport of charge carriers and pave the way for various applications such as photocatalysis and bio-sensors. Highlights: Increase of the AC conductivity with temperature and with doping type. Doping increases the defect density and so the luminescence intensity. The strong UV band is the result of the exciton recombination's and corresponds to the edge transition near the ZnO band. Enhancement of the blue and the green emission is due to oxygen vacancies.